Inheritance of halo blight resistance in common bean - Chataika, Bartholomew Y.E.; Bokosi, J.M.; Chirwa, Rowland; Kwapata, MB (2011)
Halo blight caused by (Pseudomonas syringe pv. phaseolicola (Burkh) (Psp)) is an important disease of common bean (Phaseolus vulgaris L.) world-wide. Several races of the Psp exist and likewise some sources of resistance in common bean have been identified. CAL 143, is a CIAT-bred common bean line, which was released as a variety in Malawi and several other countries in southern Africa. It possesses good resistance to Psp. However, the mode of inheritance for resistance to Psp in CAL 143, which is essential for devising a proper breeding strategy for developing bean varieties with durable resistance, has not been established. A study was conducted on the mode of inheritance for resistance to Psp using populations generated from crosses between three susceptible female parents (Chimbamba, Nasaka, and RC 15) and CAL 143 as a resistant male parent. The progenies were advanced to F2 and F3 generations in greenhouses at Bunda College of Agriculture and Bvumbwe Research Station. The F2 and F3 populations were evaluated for resistance to Psp in the field at Dedza and Ntchenachena. The results from both F2 and F3 populations indicated that there was a single dominant gene mode of inheritance for resistance to Psp in CAL 143. This monogenic resistance can be utilised easily and quickly in breeding for resistance to Psp. CAL 143 is, therefore, an ideal source of resistance and a valuable parent in breeding for resistance to Psp in Malawi.